Changes of Soil Thermal and Hydraulic Regimes in Northern Hemisphere Permafrost Regions over the 21st Century. Issue 2 (1st May 2017) - Wang, Chenghai; Wu, Di; Kong, Ying; Li, Ruolin; Shi, Hongxia
ABSTRACT: Soil moisture (SM), snow depth (SND), and air temperature are crucial factors for the soil thermal and hydraulic regimes in the permafrost regions. This paper analyzes the contribution of these factors to active layer thickness (ALT) under different climate change scenarios in northern hemisphere permafrost regions, using simulations from the Coupled Model Intercomparison Project Phase 5 (CMIP5) for the early (2016–2035, EP), middle (2046–2065, MP), and late (2080–2099, LP) periods of the 21st century. The results indicate that, with the temperature increasing, the relation between ALT and SM, SND, and mean annual air temperature (MAAT) will change in different permafrost regions. During 1986–2005 (reference period), ALT correlates significantly with SND in Europe only, the contribution of MAAT and SM to ALT are significant over the Tibetan Plateau (TP) and in North America (NA). MAAT is the only significant contribution factor to ALT deepening for all regions. In the 21st century, for the high Representative Concentration Pathways (RCP8.5), MAAT plays a dominant role in ALT over the TP and NA; however, snow effect is enhanced under RCP2.6 and RCP4.5 in Europe and NA. With temperature increasing, the importance of SM and SND alternates for low and middle emission, and gradually declines for high emission. In general, MAAT is the main contributor to ALT during the 21st century, while the impact of SM and SND declines with increasing temperature. Contribution of SM, SND, and MAAT to ALT varies, which illustrates the differences in regional thermal and hydraulic regimes from warming in permafrost regions.